Coding Analogy - Koç, Ayhan; Taşlıbeyaz, Elif (Erzincan Üniversitesi Eğitim Fakültesi Dergisi, 2024)
This study aimed to examine the pre-service teachers’ experiences in preparing and using analogies within a programming course to better understand and evaluate the concepts. The research design of this study was identified as a case study. The 21 participants of the study took an elective introductory programming (Python) course at a state university over 14 weeks. They prepared analogies during the course, and 11 of them attended a focus group interview at the end of the course. The data collection tools used in the study included a questionnaire in which learners indicated the topics they found challenging within the programming course, the analogies they created based on programming education, and interview questions that explored their views at the end of the course. These data were analyzed descriptively. The results indicated that although learners experienced difficulties in understanding algorithms, programming logic, and learning loops, the use of analogies in programming education offered positive contributions.